2009
DOI: 10.1111/j.1439-0272.1987.tb02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Localization of NADH-dependant Oxidoreductase (Diaphorase) in Boar Spermatozoa

Abstract: Investigations were carried out into the activity and localization of NADHdependant diaphorase in boar spermatozoa. Semen samples were collected from healthy boars, used in A.I. centers. The enzyme was extracted with distilled water and Triton X-100. Two forms of diaphorase were found-water-soluble and Triton X-100 soluble, showing low activity-O,36U/mI and 0,26U/ml. The enzyme was localized in the mitochondria, manifesting different intensities of reaction between sperm cells in the same ejaculate. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The oxidative enzyme NADPH‐d is also a sperm‐specific key enzyme for sperm metabolism and plays a role in sperm function through electron transfer from NAD(P)H (the promoter of sperm capacitation) to different acceptors, thereby generating ROS (Gavella et al, ). Previous studies (Atanassov et al, ; Kacheva et al, ) demonstrated that NADPH‐d enzyme activity was localized to the mitochondria in the midpiece of the spermatozoa, and Kacheva et al () suggested that low sperm motility in the buffalo may be due to low NADPH‐d activity.…”
Section: Discussionmentioning
confidence: 98%
“…The oxidative enzyme NADPH‐d is also a sperm‐specific key enzyme for sperm metabolism and plays a role in sperm function through electron transfer from NAD(P)H (the promoter of sperm capacitation) to different acceptors, thereby generating ROS (Gavella et al, ). Previous studies (Atanassov et al, ; Kacheva et al, ) demonstrated that NADPH‐d enzyme activity was localized to the mitochondria in the midpiece of the spermatozoa, and Kacheva et al () suggested that low sperm motility in the buffalo may be due to low NADPH‐d activity.…”
Section: Discussionmentioning
confidence: 98%
“…Diaphorase controls the ratio between reduced and oxidized forms of NADH; thus it takes part in the sperm energy balance (Atanassov et al 1987). This oxidoreductase is integrated with the mitochondrial respiratory chain and generates superoxide anions, affecting the level of reactive oxygen species (ROS) (Fraczek and Kurpisz 2005).…”
Section: Introductionmentioning
confidence: 99%